The Impact of ESG Disclosure on Firm Value in ASEAN: The Moderating Role of Audit Quality - Kusno, Herlambang Ramadhan; Novita, Santi (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study aims to examine the effect of ESG on firm value and the moderating role of audit quality in the ASEAN context. Using a sample of public listed companies from 2016 to 2024, data were analyzed using panel data regression. The results indicate that ESG disclosure has a significant positive effect on firm value, suggesting that sustainability transparency serves as a credible signal to investors. Furthermore, audit quality is found to positively moderate this relationship, acting as a signal enhancer and mitigates greenwashing concerns. This research contributes to signalling theory by demonstrating how audit effort reinforces the credibility in emerging markets.